MATHEMATICAL MODEL OF COVID-19 WITH VACCINE EFFICACY FACTORS - Suherman, Sofita
The transmission of COVID-19 is currently transitioning from a pandemic to an endemic status. One of the efforts that still need to be made in response to this is to maintain the vaccination program. In this paper, a model for the spread of COVID-19 will be presented by taking into account the efficacy factors of the vaccine. Two things will be considered as parameters that affect vaccine efficacy: prevention of infection and reduction of disease severity. These two issues will be discussed and simulated in this paper using Indonesia, India, and South Africa data. So that a more appropriate vaccination strategy can be given to help optimize the transition process to a post-pandemic situation based on the result of three different developing countries.